CAD/CAM silicone simulator for teaching cheiloplasty: description of the technique. Issue 2 (February 2015) - Zheng, Y.; Lu, B.; Zhang, J.; Wu, G.
Abstract Techniques of virtual simulation have been used to teach junior surgeons how to do a cheiloplasty, but still do not meet the trainees' demands. We describe a CAD/CAM silicone simulator, which we made using several maxillofacial prosthetic techniques. An optical scanning system was used to collect the data about the cleft lip. Reverse engineering software was then used to build the virtual model, and this was processed in wax by machine. The definitive simulator was made with prosthetic silicone and extrinsic colourants. The surgical trainees practised the basic skills of cheiloplasty on the simulator, and proved its worth.